Low serum testosterone is associated with adverse outcome in men with cirrhosis independent of the model for end‐stage liver disease score. Issue 11 (November 2016) - Sinclair, Marie; Gow, Paul J.; Grossmann, Mathis; Shannon, Adam; Hoermann, Rudolf; Angus, Peter W.
Abstract : Low serum testosterone has been retrospectively associated with mortality in men on the liver transplant waiting list. The impact of testosterone deficiency on other outcomes has not previously been assessed. We conducted a single center prospective observational study of all men with cirrhosis seen between 2013 and 2014. Baseline data included sex hormone profile, Model for End‐Stage Liver Disease (MELD) score, and standard biochemistry. Outcomes were recorded over 12 months including major infection, liver transplantation, and death. Of 268 cirrhotic men, the median MELD score was 10 (interquartile range [IQR], 8‐15) and median serum testosterone was 17.4 nmol/L (IQR, 8.9‐25.0 nmol/L). During the study period, 32 (12%) men died, 18 (7%) received a liver transplant, and 51 (19%) suffered a major infection. Mortality markedly increased when total testosterone fell below a threshold value of 8.3 nmol/L, and this cutoff was used for further analysis. Testosterone below 8.3 nmol/L was associated with the combined outcome of death or transplantation independently of the MELD score (hazard ratio [HR], 2.36; IQR, 1.16‐4.81; P  = 0.02) for testosterone (and HR, 1.22; IQR, 1.18‐1.27; P  < 0.001 for MELD). Low total testosterone was also an independent risk factor for major infection (HR, 3.61; IQR, 1.61‐8.06; P  < 0.001) and nearly significant for mortality alone (HR, 2.39; IQR, 0.97‐5.88; P  = 0.057). Low free testosterone (<139 pmol/L) was similarly independently associated with death or transplantation (HR, 2.43; IQR, 1.12‐5.29; P  = 0.03) and infection (HR, 3.3; IQR, 1.46‐7.46; P  = 0.004). In conclusion, low testosterone is a novel prognostic marker in men with cirrhosis that is numerically associated with increased mortality or need for transplantation, as well as risk for major infection. Interventional studies of testosterone therapy are required to investigate whether correcting low testosterone can reduce mortality and improve other clinical outcomes. Liver Transplantation 22 1482–1490 2016 AASLD .